A survey of dose tailoring methods following therapeutic drug monitoring of aminoglycoside and glycopeptides in the United Kingdom. Issue 2 (12th March 2012) - Howard, P.
Abstract : Background: The use of aminoglycoside and glycopeptide antibiotics is increasing in the UK, while cephalosporin and fluoroquinolone use is decreasing. This is in response to Clostridium difficile infection rates, and the routine screening for methicillin-resistant Staphylococcus aureus (MRSA). Dose optimisation has been shown to decrease toxicity and improve outcome. Purpose: This survey aimed to quantify the methodology to adjust narrow therapeutic spectrum antibiotics where levels are routinely done. Materials and methods: A survey was design using SurveyMonkey software. Questions were asked if and how aminoglycoside and glycopeptide doses were tailored following serum levels monitoring in adults, children and neonates. This was circulated to the members of the UKCPA Infection Management Group with a link to the web-based survey. The software analyses the submitted data. Results: There were responses from 48 different hospitals: England =41 (25% of Acute Trusts), Scotland =4, Ireland =2, Wales =1. Written guidance (or nomogram) is most commonly used for gentamicin and vancomycin, whereas dose adjustment calculation by hand was most common for tobramycin, amikacin and teicoplanin. A software program was used rarely: gentamicin=6 hospitals, tobramycin =3, amikacin =1, vancomycin =3 and teicoplanin =1. 4 centres used a program developed inhouse and two used different commercial programmes: OPT or RxKinetics. Conclusions: Within the UK, most aminoglycoside and glycopeptide dose adjustment is done using nomograms or by hand. There is very little use of commercial or inhouse software.